The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-3-319-50174-1_12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sigma-1 Receptor in Cocaine Abuse and Neurodegenerative Disease

Abstract: Sigma-1 receptors (Sig-1R) are recognized as a unique class of non-G protein-coupled intracellular protein. Sig-1R binds to its ligand such as cocaine , resulting in dissociation of Sig-1R from mitochondrion-associated ER membrane (MAM) to the endoplasmic reticulum (ER), plasma membrane, and nuclear membrane, regulating function of various proteins. Sig-1R has diverse roles in both physiological as well as in pathogenic processes. The disruption of Sig-1R pathways has been implicated as causative mechanism(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…Indeed, increase of oxidative stress in brain regions associated with the brain reward circuits (NAc, frontal cortex, and hippocampus) (Dietrich et al, 2005; Muriach et al, 2010; Jang et al, 2015) upregulates pro-inflammatory mediators (e.g., cytokines and chemokines) or astroglia/microglia activation (Renthal et al, 2009; Piechota et al, 2010; Blanco-Calvo et al, 2014; Lopez-Pedrajas et al, 2015; see review Pereira et al, 2015). Interestingly, a physiologically relevant concentration of DA that does not cause apoptosis becomes toxic in σ1R knockdown cells (Mori et al, 2012), consistent with neuroprotective and other associated positive effects of σ1R ligands activation on various chronic neurodegenerative diseases such as Alzheimer’s (Ryskamp et al, 2019) and Huntington’s diseases (Bol’shakova et al, 2017; Ryskamp et al, 2017; see review Cai et al, 2017). Indeed, σ1R agonist PRE-084 reduces oxidative species, calcium flux and other inflammatory molecules [including interleukin (IL) IL-1β, IL-6, IL-8 and tumor necrosis factor alpha (TNFα)] in various cell types (Katnik et al, 2006; Szabo et al, 2014).…”
Section: A Unifying Theorysupporting
confidence: 55%
“…Indeed, increase of oxidative stress in brain regions associated with the brain reward circuits (NAc, frontal cortex, and hippocampus) (Dietrich et al, 2005; Muriach et al, 2010; Jang et al, 2015) upregulates pro-inflammatory mediators (e.g., cytokines and chemokines) or astroglia/microglia activation (Renthal et al, 2009; Piechota et al, 2010; Blanco-Calvo et al, 2014; Lopez-Pedrajas et al, 2015; see review Pereira et al, 2015). Interestingly, a physiologically relevant concentration of DA that does not cause apoptosis becomes toxic in σ1R knockdown cells (Mori et al, 2012), consistent with neuroprotective and other associated positive effects of σ1R ligands activation on various chronic neurodegenerative diseases such as Alzheimer’s (Ryskamp et al, 2019) and Huntington’s diseases (Bol’shakova et al, 2017; Ryskamp et al, 2017; see review Cai et al, 2017). Indeed, σ1R agonist PRE-084 reduces oxidative species, calcium flux and other inflammatory molecules [including interleukin (IL) IL-1β, IL-6, IL-8 and tumor necrosis factor alpha (TNFα)] in various cell types (Katnik et al, 2006; Szabo et al, 2014).…”
Section: A Unifying Theorysupporting
confidence: 55%
“…It has been shown that σ1R agonists have ameliorative effects in several animal models of neurodegenerative disorders, such as Alzheimer's disease (Lahmy et al, 2013;Maurice and Goguadze, 2017;Ryskamp et al, 2019), Parkinson's disease (Francardo et al, 2014), Huntington's disease (Ryskamp et al, 2017), and retinal degeneration (Wang et al, 2016), whereas σ1R antagonists have pain-relief effects (Merlos et al, 2017). Accumulating evidence also suggest that σRs are critically involved in cellular adaptive mechanisms elicited by psychostimulants (Cai et al, 2017;Katz et al, 2017) and alcohol (Sabino and Cottone, 2017). Therapeutic potentials of σ1R antagonists have been explored in rodent models of cocaine or methamphetamine addiction (Hiranita et al, 2011;Robson et al, 2014;Sambo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine also induces autophagy through a nitric oxide-mediated pathway, which is thought to stimulate inflammatory and antiviral neuroprotective responses. Cocaine has a low affinity for sigma 1 receptors (Sharkey et al, 1988), which are also postulated to mediate neuroinflammation and neurogeneration during cocaine exposure (Cai et al, 2017; Guha et al, 2016). Although cocaine activates host pattern recognition receptors (PRRs), toll-like receptor 2 (TLR2) and toll-like receptor 4 (TLR4)/lymphocyte antigen 96 (MD-2) signaling complexes to modulate neuroinflammatory cytokines (Northcutt et al, 2015; Periyasamy et al, 2016), less studied is its role in regulating the protective CNS responses to viral threat, specifically activation of antiviral type I interferon signaling.…”
Section: Introductionmentioning
confidence: 99%